The new geographies of energy : assessment and analysis of critical landscapes - Zimmerer, Karl S. (London : Routledge, 2013)
Sections on energy modeling and assessment, fossil fuel landscapes, landscapes of renewable energy, and landscapes of energy consumption relate geography to the global production and consumption of energy.
Includes bibliographical references and index.
Keywords: Energy development; Energy consumption; Energy policy; Power resources